The Performance Of Employees Of The Bandung Civil Service Police Unit (Satpol PP) In The Implementation Of Illegal Advertising Control Insidentil And Permanent In 2020 Base On Administrative Law - Yeti Rohayati; Diani Indah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Along with the progress and development of the business world in Indonesia, especially the city of Bandung, the more advanced the establishment of billboards both isidentil and permanent. The installation of billboards is currently increasing in number and piling up without paying attention to the predetermined procedures for organizing billboards. So it is necessary to carry out supervision or control, this regulation is an obligation of the Bandung City Civil Service Police Unit (Satpol PP) as stated in the Bandung City Regional Regulation Number 02 of 2017 in Article 19 paragraph (1) Challenge the implementation of the regulation of the implementation of advertising. However, in reality, in the implementation of billboards, there are still many people who do not follow the installation procedure and not all violations of billboard organizers can be put in order by satpol PP Bandung City. The purpose of this study is to determine the performance of Satpol PP Bandung City employees in the Regulation of Billboards 2020 and  to find out the supporting and inhibiting factors in the control of violations of billboard organizers in Satpol PP Bandung City.  The method used in this study is a descriptive method with a qualitative type of research. This is done in the context of collecting primary data by means of observation, interviews and documentation. In addition, data collection was carried out using several book references with research themes to support previous data. The results showed that the performance of Satpol PP Bandung City Employees in the Implementation of Billboard Control has not been optimal, this is evidenced by the many violations of billboard organizers in the city of Bandung. This is due to the lack of personnel and facilities and infrastructure. The way to overcome this is that there must be additional personnel or employees of billboard control and the provision of adequate equipment to support the implementation of advertising control in the field  TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//   This page is in English Translate to Indonesian    AfrikaansAlbanianAmharicArabicArmenianAzerbaijaniBengaliBulgarianCatalanCroatianCzechDanishDutchEnglishEstonianFinnishFrenchGermanGreekGujaratiHaitian CreoleHebrewHindiHungarianIcelandicIndonesianItalianJapaneseKannadaKazakhKhmerKoreanKurdish (Kurmanji)LaoLatvianLithuanianMalagasyMalayMalayalamMalteseMaoriMarathiMyanmar (Burmese)NepaliNorwegianPashtoPersianPolishPortuguesePunjabiRomanianRussianSamoanSimplified ChineseSlovakSlovenianSpanishSwedishTamilTeluguThaiTraditional ChineseTurkishUkrainianUrduVietnameseWelsh Always translate English to IndonesianPRO Never translate English Never translate jurnal.unikal.ac.id